2014
DOI: 10.1111/jsm.12446
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in the Treatment of Penile Prosthesis Infections by Explantation Alone vs. Immediate Salvage and Reimplantation

Abstract: Introduction A penile prosthesis infection (PPI) is either treated with explantation of the prosthesis with a possible delayed reimplantation or a salvage procedure with an immediate reimplantation of the prosthesis. Aim We used a large, all-payer national database to investigate the use of the salvage procedure in the setting of PPI. Methods The study used y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Seventeen (31%) men elected to undergo replacement of their malleable device with an inflatable prosthesis occurring on average 6.7 months after their initial washout surgery. The authors found that the patients who elected IPP replacement were typically younger by 10 years which is in line with the findings by Zargaroff et al ( 24 ). The average follow-up for Gross’ multicenter cohort was only 8.4 months so longer follow-up may find a higher proportion of men proceeding with IPP replacement.…”
Section: Malleable Rod Salvagesupporting
confidence: 86%
See 1 more Smart Citation
“…Seventeen (31%) men elected to undergo replacement of their malleable device with an inflatable prosthesis occurring on average 6.7 months after their initial washout surgery. The authors found that the patients who elected IPP replacement were typically younger by 10 years which is in line with the findings by Zargaroff et al ( 24 ). The average follow-up for Gross’ multicenter cohort was only 8.4 months so longer follow-up may find a higher proportion of men proceeding with IPP replacement.…”
Section: Malleable Rod Salvagesupporting
confidence: 86%
“…Despite the excellent results demonstrated with Mulcahy salvage and especially with malleable rod salvage, a recent study by Zargaroff et al analyzing the national trends in treatment of IPP infections found a surprisingly low rate of salvage procedures are being performed ( 24 ). Utilizing the Nationwide Inpatient Sample database from 2000 to 2009, they reported that 82.7% of infected IPPs were treated with explantation alone while only 17.3% underwent an immediate salvage procedure.…”
Section: Malleable Rod Salvagementioning
confidence: 99%
“…A penile prosthesis infection may be either treated with explantation of the prosthesis with a possible delayed reimplantation or a salvage procedure with an immediate reimplantation of the prosthesis. In a total of 1 557 patients treated with an explantation only (82.7 %) or salvage (17.3 %) comorbid diabetes did not independently affect the salvage rate of penile prosthesis infection (Zargaroff et al, 2014).…”
Section: Penile Implantsmentioning
confidence: 88%
“…Our practice mimics others in this regard. A recent study of implant infections in the USA found only 15% were offered salvage ( 9 ).…”
Section: Complications and Lessons Learnedmentioning
confidence: 99%